Rodolfo Jacobson: The English Record. Studies in English to Speakers of Other Languages and Standard English to Speakers of a Non-Standard Dialect. Vol. XX. núm. 4 - Paulín de Siade, Georgina (Revista Mexicana de Sociología, 2024)
-